2017
DOI: 10.1051/0004-6361/201628552
|View full text |Cite
|
Sign up to set email alerts
|

Galactic cold cores

Abstract: Context. The onset of star formation is intimately linked with the presence of massive, unstable filaments. These structures are therefore key for theoretical models aiming to reproduce the observed characteristics of the star formation process. Aims. As part of the filament study carried out by the Herschel Galactic Cold Cores Key Programme, here we study the filament properties presented in GCC VII (Paper I) in context with theoretical models of filament formation and evolution. Methods. A conservative sampl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…We also note that filaments embedded in high column density environments tend to have higher column densities. The same behavior was observed in Herschel data at smaller scales (Rivera-Ingraham et al 2017), where dense filaments tend to be embedded in dense environments.…”
Section: Column Density Subsamplessupporting
confidence: 82%
“…We also note that filaments embedded in high column density environments tend to have higher column densities. The same behavior was observed in Herschel data at smaller scales (Rivera-Ingraham et al 2017), where dense filaments tend to be embedded in dense environments.…”
Section: Column Density Subsamplessupporting
confidence: 82%
“…WR 18 would then be the result of a large clump that was triggered into star formation by a passing wave of material. There are numerous examples of triggered clumps of this kind in Herschel observations (Hill et al 2011;Rivera-Ingraham et al 2015;Zavagno et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Filaments appear to be highly dynamic entities. Rivera-Ingraham et al (2017) have shown evidence that the filaments evolve from a subcritical (i.e., stable; Inutsuka & Miyama 1992) to a supercritical (i.e., unstable) regime by accretion of material from their environment according to recent observations of nearby (d < 500 pc) filaments (Rivera-Ingraham et al 2016). They found that self-gravitating filaments in dense environments (Av ∼ 3, N H2 ∼ 2.9 × 10 20 cm −2 ) can become supercritical on timescales of ∼ 1 Myr, and suggested that filaments evolve in tandem with their environment.…”
Section: Molecular Cloud Substructure and Star Formationmentioning
confidence: 99%